The potency of bay leaves extract (Syzygiumpolyanthum) as anti-inflammation in Rattus norvegicus induced with Complete Freund’s Adjuvant - Buana, Dwi Candra; Sudiana, I Ketut; Nugraha, Jusak (POLTEKKES KEMENKES YOGYAKARTA, 2019)
The using of herbal plants in Indonesia as medicine based on traditional knowledge. One of the herbal plants that believed has medication effect is bay leaves (Syzygiumpolyanthum). Bay leaves contain a flavonoid that can prevent inflammation. The study aims to prove the potency of bay leaves extract to prevent the inflammation, which is indicated by decreasing the paw edema thickness in rat induced with Complete Freund's Adjuvant (CFA). This study used 25 animal models of male rat (Rattus norvegicus) strain Wistar that divided into five groups, one group for a normal group (no treatment), one group for positive control which was injected with CFA sub plantar and given treatment with Na CMC and three test groups which is got three different doses of bay leaves extract peroral and the doses were 100 mg/kg BW, 300 mg/kg BW, 400 mg/kg BW, and injected with CFA into the sub plantar. Bay leaves extract was given one hour per oral before injected with CFA. The measurement of paw edema was done at 24 hours after CFA injection. The result of this study showed that bay leaves extract gave the anti-inflammation effect to the rats which were injected with CFA. It is concluded that bay leaves extract containing flavonoids plays a role in inhibit cytokines proinflammatory synthesis.